Umetnost za vse - Kermauner, Aksinja (Revija za elementarno izobraževanje, 2014)
Art for All. The aim of spatial planning on the principles of “design for all” is to ensure that every individual, regardless of obstacle, can participate in the information society. It combines the principles of how as many people as possible could use products, services and systems without adjusting them. Why should we not transfer the concept of “design for all” also to other areas, such as the field of art? In this article we consider how a work of art, especially a two-dimensional one, could be adapted for blind or visually impaired visitors of a gallery or to a museum, and list what has already been done in this area. We also describe a textbook for teaching fine arts, adapted for blind and partially sighted students.